1997
DOI: 10.1136/bmj.315.7104.341
|View full text |Cite
|
Sign up to set email alerts
|

Reduced final height and indications for insulin resistance in 20 year olds born small for gestational age: regional cohort study

Abstract: Objective: To assess the role of polymerase chain reaction in defining infectiousness among people infected with hepatitis C virus. Design: Published studies of hepatitis C transmission were examined. Twenty nine studies with identified sources of hepatitis C infection who were tested for presence of hepatitis C RNA by polymerase chain reaction were reviewed, including studies of vertical transmission (n = 21), transmission after transplantation (n = 3), transfusion of blood components (n = 3), and needlestick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
227
4
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(252 citation statements)
references
References 52 publications
(70 reference statements)
14
227
4
7
Order By: Relevance
“…Several studies have shown that shorter stature is associated with higher 2hPG levels, [1,[18][19][20], and genetic or pre-and postnatal environmental factors have been suggested as explanatory mechanisms [21,22]. If the association between height and 2hPG levels is causally related to inherent metabolic abnormalities, we would expect HbA 1c levels to also be affected by height.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that shorter stature is associated with higher 2hPG levels, [1,[18][19][20], and genetic or pre-and postnatal environmental factors have been suggested as explanatory mechanisms [21,22]. If the association between height and 2hPG levels is causally related to inherent metabolic abnormalities, we would expect HbA 1c levels to also be affected by height.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the inconstancy of the association between low birthweight or SGA and the other parameters of MS especially in young subjects [7,8,10,21,22]. It is likely that, although the association between insulin resistance and reduced fetal growth is constant, the expression and/or age at onset of the other parameters of the MS depend on the degree of genetic predisposition or on the postnatal environmental circumstances observed in the different study populations.…”
Section: Bmi (Sds)mentioning
confidence: 97%
“…The association between a low birthweight and the metabolic syndrome (MS) [1][2][3] or with one of its components has been substantially documented in various populations [4][5][6][7][8][9][10]. MS was originally described in humans to cluster with insulin resistance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects born small for gestational age (SGA) who are prone to develop insulin resistance in adulthood [1][2][3][4][5] display an abnormal development pattern of the adipose tissue during fetal and postnatal life by showing a dramatically reduced body fat mass at birth and, in the large majority of them, a catch-up growth process during infancy and childhood involving the adipose tissue. [6][7][8] Since adipose tissue plays a key role in the development and the worsening of insulin resistance, 9,10 this very peculiar pattern of development of the adipose tissue itself might contribute to the later development of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%